Developments in TEM Nanotomography of Calcium Silicate Hydrate. Issue 7 (15th April 2015) - Taylor, Rae; Sakdinawat, Anne; Chae, Sejung R.; Wenk, Haz‐Rudolf; Levitz, Pierre; Sougrat, Rachid; Monteiro, Paulo J.M.; Jennings, H.
<x xml:space="preserve">Abstract</x> This investigation was designed to explore the possibility of using transmission electron microscope (TEM) tomography on cement‐based systems gain a greater understanding of their nanostructure and pore network. The preliminary results show a clearly a well‐defined pore network at the nanoscale, with pore size approximately 1.7–2.4 nm in diameter and spaced around 5–8 nm apart. A comparison of small angle X‐ray scattering data with 2‐D TEM images analyzed with the Fourier slice theorem documents an excellent structural correlation.